Citizen preferences for possible energy policies at the national and state levels. (October 2018) - Peterson, Mark; Feldman, David
Abstract: Without knowledge of citizen preferences, policy makers most often rely on their intuition to infer such preferences or on biased information provided by special interest groups. Using a choice-modeling approach, the study features two large-scale, field-research projects—one done nationally in the US, and another composed of separate data collection efforts across eight states where energy policies have a high profile in public discourse. The results suggest four outcomes of energy policies are most important to citizens at the national level: 1) environmental quality, 2) energy costs, 3) job creation, and 4) greenhouse gas emissions. This pattern of importance for the outcomes of energy policy persists across important demographic groups including those related to political-party affiliation. At the state level, the four preferred outcomes of energy policies seen at the national level also appear—although in a different order of preference in some states. Further analysis of citizens' willingness to change energy policy at the state level suggests that risk aversion characterizes citizens' views about revising energy policy. Highlights: Researchers derived importance weights for eight components of federal-energy-policies. Researchers found the most important component was impact on environmental quality. Researchers did a similar study in eight states with active energy-policy discussions. The most important energy policies across the states related to the environment and energy costs. Analysis disclosed citizens' pronounced risk-aversion for negative policy changes.